The State of Inventory Accounting and Directions for its Improvement - Khusanovich, Turaboev Temurbek (International Journal on Orange Technologies, 2023)
This article provides an in-depth exploration of inventory accounting practices and their importance in business operations. The article reviews traditional and modern inventory accounting methods, highlighting their advantages, disadvantages, and common challenges. It also examines the classification and categorization of inventory, emphasizing the benefits of accurate categorization and providing examples of inventory classification systems. Additionally, the article delves into inventory valuation methods, comparing FIFO, LIFO, and weighted average approaches. It explores costing techniques, including absorption costing, direct costing, and activity-based costing (ABC), along with the allocation of overhead costs. The article emphasizes the significance of real-time tracking in inventory control and discusses various tracking technologies such as barcodes and RFID. It also explores the integration of inventory accounting with supply chain management systems and examines the impact of emerging technologies, automation, and artificial intelligence on inventory management. Finally, the article offers insights into potential future trends and developments in the field of inventory accounting. By following the recommendations provided, businesses can improve their inventory accounting practices, enhance accuracy, optimize inventory levels, and make informed decisions for better financial performance.